CLINICAL OUTCOME MEASURES OF PSORIASIS - E. Berardesca; C. Bonifati (PAGEPress Publications, 2011)
Several tools have been introduced in clinical trials to quantify the severity and the response to a given therapeutic regimen of both psoriasis and psoriatic arthritis. Each method present specific advantages and limitations. Here we will discuss some of the most popular clinical outcome measures of both psoriasis (Psoriasis Severity Index, Physician Global Assessment, National Psoriasis Fundation-Psoriasis Score, Dermatology Life Quality Index) and psoriatic arthritis (American College Rheumatology response criteria, Psoriatic Arthritis Response Criteria). Key words: Psoriasis, psoriatic arthritis, outcome